On the Importance of the Polarity for GaN/InGaN Last Quantum Barriers in III-Nitride-Based Light-Emitting Diodes - Zi-Hui Zhang; Yonghui Zhang; Hongjian Li; Shu Xu; Chong Geng; Wengang Bi (IEEE Photonics Journal)
In this paper, we investigate the electron injection efficiency in terms of different polarities and different polarization charge densities at the ${\rm{GaN/ InGaN}}$ interface. We find that the growth orientation for the ${\rm{GaN/ InGaN}}$ -type last quantum barrier is essentially vital, i.e., the ${\rm{GaN/ InGaN}}$ -type last quantum barrier is not able to effectively reduce the electron leakage and will degrade the light-emitting diode (LED) performance when the ${\rm{GaN/ InGaN}}$ interface is [000–1] polarized. However, a suppressed electron leakage and enhanced optical power can be obtained for III-nitride LEDs grown along the [0001] orientation when the ${\rm{GaN/ InGaN}}$ interface possesses polarization-induced negative charges. We conclude that the polarization-induced negative charges at the [0001] oriented ${\rm{GaN/ InGaN}}$ interface facilitate the surface depletion in the GaN region, i.e., the conduction band of the GaN region is bent in the way of favoring electron depletion and contributes to an enhanced conduction band barrier height for electrons.